Efforts to Improve Class III PKN Learning Outcomes Using the PBL Model Assisted by the Pancasila Smart Board at SDN Tambakmas 2 Magetan - Repi Putri Prasetyana; Sardulo Gembong; Albertus Prakoso Lelono (STKIP Taman Siswa Bima, 2023)
The background of this research is the low PKN learning outcomes of class III students at SDN Tambakmas 2 Magetan, for this reason learning improvements are carried out by conducting classroom action research using the PBL learning model assisted by the Pancasila intelligenta board media. This study aims to improve PKN learning outcomes using the PBL learning model assisted by Pancasila smart board media in class III students at SDN Tambakmas 2 Magetan. This research is a class action research conducted in class III SDN Tambakmas 2 Magetan. The subjects in this study were class III students at SDN Tambakmas 2 Magetan, totaling 10 children. This research was carried out in 2 cycles. The results showed that there was an increase in PKN learning outcomes for class III students at SDN Tambakmas 2 Magetan. This can be seen based on the increasing student test scores in cycle I and cycle II. In the first cycle, the average learning result was 63% and in the second cycle it increased to 95%. Thus it can be concluded that using the PBL learning model assisted by the Pancasila Smart Board media can improve the learning outcomes of class III students at SDN Tambakmas 2 Magetan.